The Influence of Transformational Leadership Style and Work Motivation on Employee Performance in Manufacturing Companies in Indonesia - Vika Fransisca (PT. Publikasiku Academic Solution, 2025)
The phenomenon of product returns has become a crucial issue in modern supply chain management, particularly in the digital era, when consumers are increasingly critical of product and service quality. The high rate of returns impacts operational efficiency, logistics costs, and a company's brand image. In the context of the Indonesian e-commerce and retail industry, product returns management has not been optimally managed, necessitating an evaluative model to understand the factors influencing consumer return decisions. This study aims to analyze factors influencing customer return intention, including perceived product quality, clarity of product information, consumer trust, and previous purchasing experience. A quantitative approach was employed, using a survey method, distributing questionnaires to 150 respondents who had made online purchases. Data analysis was performed using Partial Least Squares (PLS)-based Structural Equation Modeling (SEM) using SmartPLS 4 software to examine the relationships between variables and their strengths. The results show that perceived product quality and clarity of information have a significant positive effect on consumer trust, which in turn influences product return intention. Meanwhile, a poor purchasing experience strengthens the tendency for consumers to make returns. These findings underscore the importance of transparency and product quality control in reducing return rates on Indonesian e-commerce platforms.